Editorial Note (American Journal of Islam and Society, 1985)
The members of the editorial staff of the AJISS were very encouraged bythe response from readers after the release of Volume 2, Number 1 of thejournal. Apparently many readers were impressed by the new name and thenew format. Some readers see the new name of the journal as a challengeto Muslim social scientists to take a stand on important human issues andto conduct their research and analyses within an Islamic framework. One readerreminded me of an article written by James M. Gustafson on “Man In Lightof Social Science and the Christian Faith.” Apparently this Christian authorwas concerned about some of the same philosophical and epistemological issuesthat stir us in this journal. This is to say, as a Christian thinker, Gustafsonclaims the right “to interpret man from the Christian perspective as well,and. . .sees things in this light that the lights from the social science do notexpose.” Regardless of how some of the social scientists in the academic communityview statements like that of Gustafson’s, the fact remains that thosewho believe in a sublunar world (Dunya) and a transcendenA world (al-Akhira)will always adopt critically the methods and research findings of the secularsocial science.In this volume we have a number of interesting and infromative articlesthat raise a host of issues about the Islamic experience. The lead article iswritten by Roger Garaudy, a French Muslim who takes a critical look at theWestern philosophical tradition from the perspective of a Muslim student ofhuman knowledge. His analysis is a part of the beginning of Western Muslimattempts to probe deeply into their own intellectual tradition in light of theirunderstanding of their Muslim intellectual heritage. Following Garaudy’s paperare several other papers dealing with Ibn Hazem, Amir Ali, Ibn Khaldun andMawlana Mawdudi. The Ibn Hem’s piece treats us to a careful analysisthinker’s thought on Qiyas in Islamic law; Amir Ali’s article addresses theMuslim thinkers views of Islam early in this century; the Ibn Khaldun essaygives us an alaysis of the North African Muslim’s under.,tanding of perceptiontheories of his time; the Mawdudi piece treats us to a careful analysisof the Pakistani Muslim writer’s tafsir of the Holy Qur’an. The article of Z.I.Ansari provides an analysis of the life and activities of Imam Mrith DeenMuhammad, the successor of the late Honorable Elijah Muhammad and oneof the leading MusIim figures in America today ...